The history of the Jews in the Greco-Roman world - Schäfer, Peter, 1943- (Routledge, 2003)
Examines Judaism in Palestine throughout the Hellenistic period, from Alexander the Great's conquest in 334 BC to its capture by the Arabs in AD 636.